Polyurethane foam, preparation method thereof and refrigerator

Through the limited mixing steps and material characteristics of the refrigerator bubble preparation, the problem of poor uniformity of the aquarrings foam waste -activated micro powder in high -viscosity white material is solved, and the high -performance preparation of hard polyurethane foam is realized to meet the insulation and structure of the refrigerator. Require.

CN119371622APending Publication Date: 2025-01-28HISENSE(SHANDONG)REFRIGERATOR CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411483990.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

When preparing rigid polyurethane foam for refrigerators, the urethane foam waste activated powder has poor uniformity in high viscosity white materials, easy clogging of equipment filters and difficulty in powder settlement, which cannot meet the foam performance requirements of the refrigerator.

Method used

Through the characteristics of limited mixture steps and polyether polyols and activated hard foam microfream, multi -directional shear and high mixing speed mud equipment are adopted, combined with stress hybrid and specific foaming agents to ensure activated hard bubble microfana powder Uniform mixing in white material.

Benefits of technology

The low -K value, low density, high strength, good modeling, and good adhesion of polyurethane foam are realized, and the problem of equipment filter blocking and powder settlement is solved, and the refrigerator's requirements for foam performance are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371622A_ABST
    Figure CN119371622A_ABST
Patent Text Reader

Abstract

The invention discloses polyurethane foam, a preparation method thereof and a refrigerator, and belongs to the field of polyurethane foam materials. The material mixing step comprises the following steps: mixing polyether polyol, water, a catalyst and a foaming aid to obtain a first mixture; mixing a high-boiling-point foaming agent into the first mixture to obtain a second mixture; adding the activated hard foam micro powder into the second mixture, performing pressure-maintaining mixing in mixing equipment, adding a low-boiling-point foaming agent, and continuing pressure-maintaining mixing to obtain a third mixture; the polyurethane foam waste activated micro-powder is applied to the aspect of refrigerator foam materials, and the problems that when polyurethane foam waste activated micro-powder is used as a raw material for preparing rigid polyurethane foam used for refrigerators, the uniformity of the polyurethane foam waste activated micro-powder mixed into white materials is poor, a filter screen of equipment is blocked, and powder is settled are solved; the prepared polyurethane foam has the characteristics of being low in K value, low in density, high in strength, good in demolding property and good in adhesion, the preparation method of the polyurethane foam and the refrigerator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyurethane foam materials, and in particular relates to polyurethane foam, a preparation method thereof and a refrigerator. Background Art

[0002] As a highly efficient thermal insulation material, polyurethane foam is widely used as an insulation layer in the production of refrigerators, freezers, and water heaters. Its foam physical properties and production process performance cannot be completely replaced by other materials in the future. At present, the recycling of polyurethane foam waste is mainly divided into physical and chemical methods. The ordinary physical method has a simple process and low cost, mainly including hot pressing molding, extrusion molding, and filler method, but the treated waste is not reactive and can only be used for low-end product manufacturing in the future. Compared with the physical method, the chemical method has received more attention in recent years. Its basic principle is that polyurethane foam will depolymerize under chemical degradation agents and specific conditions, and gradually crack into the original reactants or other oligomers, which are used as raw materials for polyurethane reproduction. Common chemical recovery methods include hydrolysis, aminolysis, acidolysis, alcoholysis, and glycolysis. However, the existing methods all require special chemical equipment, complex equipment and processes, high investment and production costs, and low added value.

[0003] Chinese patent CN113817128A discloses a rigid polyurethane foam plastic and its preparation method and application, and specifically discloses: the activated micropowder of urethane foam waste is obtained by mechanical shearing of polyurethane foam waste; the mechanical shearing temperature is 50-85°C, and the line speed is 10-60m / min; the particle size of the activated micropowder of polyurethane foam waste is ≤65μm; the polyol includes one or more of polyester polyol, polyether polyol, polybutadiene polyol, polycarbonate polyol, rosin ester polyol and castor oil; the hydroxyl value of the polyol is ≥70mgKOH / g, and the viscosity is ≤1000Pa / s. This patent uses the activated micropowder of polyurethane foam waste to replace part of the polyol to prepare rigid polyurethane foam plastic, realizing the high added value resource utilization of polyurethane waste, and the prepared rigid polyurethane foam plastic has excellent performance.

[0004] However, the rigid polyurethane foam used in refrigerators has high requirements on the strength and demolding efficiency of the rigid polyurethane foam. Therefore, the viscosity of the polyol used to prepare the rigid polyurethane foam is required to be not less than 1000 Pa / s. However, at this viscosity, it is impossible to solve the problems of uniformity of mixing the activated micropowder of urethane foam waste into the white material, clogging of the equipment filter and sedimentation of the powder. Summary of the invention

[0005] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to overcome the problems of uniform mixing of activated micropowder of waste urethane foam into white material, clogging of equipment filter screen and powder sedimentation when the activated micropowder of waste urethane foam is used as a raw material for preparing hard polyurethane foam for use in refrigerators, and to propose a polyurethane foam that can ensure that the activated micropowder of waste urethane foam is uniformly mixed in high-viscosity white material without agglomeration and sedimentation, and the prepared polyurethane foam has the characteristics of low K value, low density, high strength, good demoulding property and good adhesion, as well as a preparation method and a refrigerator.

[0006] In order to solve the technical problem, the technical solution adopted by the present invention is:

[0007] In one aspect, the present invention provides a method for preparing polyurethane foam, wherein the method comprises preparing polyurethane foam for use as refrigerator foam, comprising a mixing step, wherein the mixing step further comprises:

[0008] The first mixture preparation step comprises mixing polyether polyol, water, a catalyst and a foaming aid to obtain a first mixture;

[0009] A second mixture preparation step, comprising mixing a high boiling point blowing agent into the first mixture to obtain a second mixture;

[0010] The third mixture preparation step comprises adding the activated rigid foam powder to the second mixture, and adding a low-boiling point foaming agent after mixing under pressure in a mixing device, and continuing to mix under pressure to obtain a third mixture; during the preparation of the third mixture, the mixing device provides multi-directional shear force to the mixture and maintains a stirring state, the stirring speed is greater than 1000 rpm, the mixing temperature is greater than 10°C, and the pressure of the pressure-maintaining mixing is greater than 2 bar;

[0011] The viscosity of the polyether polyol is greater than 1000 mPa.s; the activated rigid foam micropowder is obtained by crushing rigid polyurethane foam waste and has terminal active hydroxyl groups, and the particle size distribution DV(90) of the activated rigid foam micropowder is ≤150 μm.

[0012] Preferably, the high-boiling-point foaming agent is a foaming agent with a boiling point greater than 5°C, and the low-boiling-point foaming agent is a foaming agent with a boiling point less than 0°C.

[0013] Preferably, the high boiling point foaming agent is selected from at least one of cyclopentane, isopentane, 245FA, and LBA; the low boiling point foaming agent is selected from at least one of R600 and R600a.

[0014] Preferably, during the preparation of the third mixture, the mixing temperature is ≥30° C., the pressure of the pressure-maintaining mixing is >4 bar, and the mixing time is ≥30 minutes.

[0015] Preferably, the method further comprises a foaming step, wherein the foaming material temperature in the foaming step is ≥25°C and the gun tip pressure is ≥140 bar.

[0016] Preferably, the composition comprises, by weight, 70-100 parts of polyether polyol, 1-30 parts of activated rigid foam powder, 1-25 parts of foaming agent, 0.1-2.3 parts of water, 0.1-5 parts of catalyst and 0.1-2.5 parts of surfactant.

[0017] Preferably, the polyether polyol is prepared by reacting an initiator and an olefin oxide; the olefin oxide is selected from one or more of propylene oxide, ethylene oxide, and butylene oxide; the initiator is selected from a compound containing active hydrogen; the compound containing active hydrogen is selected from one or more of o-toluenediamine, sucrose, glycerol, vegetable oil, trimethylolpropane, pentaerythritol, sorbitol, xylitol, mannitol, methyl glucoside, ethylenediamine, and triethanolamine; the comprehensive functionality of the polyether polyol is greater than 3, and the hydroxyl value is greater than 350.

[0018] Preferably, the catalyst comprises a composition of a foaming catalyst, a gel-type catalyst and a polymerization catalyst; the foaming catalyst is selected from at least one of pentamethyldiethylenetriamine, bis-dimethylaminoethyl ether, N-methyldicyclohexylamine and tetramethylhexanediamine; the gel-type catalyst is 1,2-dimethylimidazole or a mixture of 1,2-dimethylimidazole and at least one of dimethylcyclohexylamine and dimethylbenzylamine; the polymerization catalyst is selected from at least one of isooctyl ester, potassium acetate, 1,3,5-tris(dimethylaminopropyl)hexahydrotriazine, (2-hydroxypropyl), trimethylammonium formate, ethyl quaternary ammonium salt and octyl quaternary ammonium salt; the surfactant is selected from at least one of silicone oil L6863, silicone oil L6988, L-6952, silicone oil AK8830, silicone oil B8525, silicone oil B8545, AK8812 of Meside or AK8809 of Meside.

[0019] Another aspect of the present invention provides a polyurethane foam, which is prepared by the method for preparing the polyurethane foam described in any of the above technical solutions.

[0020] The present invention also provides a refrigerator, wherein the foam of the refrigerator is selected from the polyurethane foam described in the above technical solution.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The invention provides a method for preparing polyurethane foam. By limiting the mixing step and combining the limitations on polyether polyol and activated rigid foam micropowder, the method not only meets the requirements of refrigerators for polyurethane foam performance, but also realizes uniform mixing of activated rigid foam micropowder in white material, avoids the occurrence of equipment filter screen clogging and powder sedimentation problems, and ensures that the prepared polyurethane foam has the characteristics of low K value, low density, high strength, good demoulding property and good adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM image of the activated rigid foam micropowder provided by the present invention;

[0024] Figure 2 This is a SEM image of the foam containing activated rigid foam micropowder provided by the present invention;

[0025] Figure 3 This is a SEM image of the foam provided by the present invention that does not contain activated rigid foam micropowder;

[0026] Figure 4 This is the infrared spectrum of the activated rigid foam micropowder provided by the present invention. DETAILED DESCRIPTION

[0027] The technical scheme in the specific embodiment of the present invention is described in detail and completely below. Obviously, the described embodiment is only a part of the specific implementation of the overall technical scheme of the present invention, rather than all implementations. Based on the overall concept of the present invention, all other embodiments obtained by ordinary technicians in this field fall within the scope of protection of the present invention.

[0028] In one aspect, the present invention provides a method for preparing polyurethane foam, wherein the method comprises preparing polyurethane foam for use as refrigerator foam, comprising a mixing step, wherein the mixing step further comprises:

[0029] The first mixture preparation step includes mixing polyether polyol, water, a catalyst and a foaming aid to obtain a first mixture.

[0030] The second mixture preparation step comprises mixing a high boiling point blowing agent into the first mixture to obtain a second mixture.

[0031] The step of preparing the third mixture comprises adding activated rigid foam powder to the second mixture, adding a low-boiling point foaming agent after mixing under pressure in a mixing device, and continuing mixing under pressure to obtain a third mixture; during the preparation of the third mixture, the mixing device provides multi-directional shear force to the mixture and maintains a stirring state, the stirring speed is greater than 1000 rpm, the mixing temperature is greater than 10°C, and the pressure of the pressure-maintaining mixing is greater than 2 bar; in a preferred embodiment, the mixing temperature is greater than 30°C, the pressure of the pressure-maintaining mixing is greater than 4 bar, and the mixing time is greater than 30 minutes. Among them, the above-mentioned mixing equipment is a solid-liquid-gas three-phase mixing equipment. The core technical point of the mixing step lies in the control of the core parameters of the mixing. First, the particle size distribution requirement of the mixed active rigid foam micropowder is DV(90)≤150 microns. Second, the mixing temperature requires the material temperature ≥10°C (reducing the viscosity of the liquid system and making it easier to evenly disperse the powder). Third, the mixing process is carried out under pressure maintenance conditions (air or nitrogen pressure maintenance) (preferably >2bar, the main purpose is to increase the dissolution of the foaming agent component, especially the foaming agent with a lower boiling point, in the polyether polyol and reduce the volatilization of the component); fourth, the mixing equipment can provide shear forces in four directions (vertical and parallel directions) of up, down, left and right during the mixing process. The stirring speed is preferably >1000 rpm. Ultrasound and other methods can also be used to help disperse the powder, further reduce the viscosity and enhance the uniform dispersion effect. Fifth, the mixing time is ≥30 minutes. Any equipment that can realize the above-mentioned mixing process can be used, and there is no requirement for the mixing equipment. However, only the mixing step that meets the above-mentioned 5 conditions can achieve the uniform mixing of the polyether polyol and the active rigid foam micropowder system defined in the technical solution.

[0032] The viscosity of the polyether polyol is greater than 1000 mPa.s; the activated rigid foam micropowder is obtained by crushing rigid polyurethane foam waste and has terminal active hydroxyl groups, and the particle size distribution DV(90) of the activated rigid foam micropowder is ≤150 μm.

[0033] It should be noted that the rigid polyurethane foam used in refrigerators has high requirements for the strength and demoulding efficiency of the rigid polyurethane foam. Therefore, the viscosity of the polyol used to prepare the rigid polyurethane foam is required to be no less than 1000Pa / s. However, under this viscosity, the existing technology cannot solve the problems of uniform mixing of activated micropowder of urethane foam waste into white material, clogging of equipment filter and sedimentation of powder. The above technical scheme limits the mixing steps and limits the particle size distribution of activated rigid foam micropowder, which not only achieves uniform mixing of activated rigid foam micropowder in the system with a viscosity of polyether polyol greater than 1000mPa.s, but also ensures that the prepared polyurethane foam can meet the performance requirements of refrigerators for foam. Furthermore, the above technical scheme strictly limits the mixing order of the mixing process. The reason is that the present invention first mixes the foaming aid and the high-boiling point foaming agent to obtain the first and second mixtures, which can effectively reduce the viscosity of the system before mixing the activated hard foam micropowder. When mixing the activated hard foam micropowder, the powder can be mixed into the combined white material more quickly and evenly under stirring conditions. The whole is not prone to problems such as agglomeration and sedimentation, and the mixing efficiency is greatly saved. Finally, the low-boiling point foaming agent is mixed to further reduce the overall viscosity of the foam material combined white material. In addition, the present invention realizes the recycling of rigid polyurethane foam for waste refrigerators by limiting the mixing step, that is, the above-mentioned activated rigid foam powder is obtained by crushing the rigid polyurethane foam for waste refrigerators, and the uniformity requirement of the particle size after crushing is relaxed, and the particle size distribution only needs DV (90) ≤ 150 μm to meet the requirement; at the same time, the polyether polyol in the white material system of the present invention is selected with a viscosity greater than 1000 monomers to meet the requirements of high strength, demolding efficiency, etc., and the foaming agent selection includes but is not limited to CP, 245FA, LBA, 152a, 134a, R600, R600a, trifluoropropylene and other single or combined multi-component foaming systems, so the demolding property is better, the density is lower, the K value, the strength performance, etc. are better, and the selection of high viscosity and high functionality monomers has a better foam closed cell rate and better bonding performance.

[0034] The present invention adopts mechanical force and physical and chemical methods to make activated rigid foam micropowder from the residual polyurethane rigid foam, which is used to replace part of the polyol for re-foaming. This method can realize the high-value recycling of the residual materials and waste materials of the polyurethane thermal insulation layer rigid foam production line, which helps to reduce production costs. The most fundamental feature that distinguishes the present invention from the preparation of powder by ordinary physical methods is that the chemical bonds of the powder are broken, generating -OH groups that can further react with the iso-NCO-groups in the black material. Specifically, the above-mentioned activated rigid foam micropowder is obtained by crushing the rigid polyurethane foam waste through a crushing equipment that generates mechanical shear force during crushing. The activated rigid foam micropowder meets two conditions. One is that the particle size distribution DV (90) is ≤150μm, and the uniform particle size distribution is conducive to good compatibility with the combined white material; the second is that there is hydrogen bond breaking and decomposition of the carbamate group in the high-intensity tensile extrusion stress field. The decomposition product contains -OH structure, which can react with isocyanate during foaming. Figure 1As shown in the figure, the pore structure of the activated hard foam powder is no longer visible, indicating that the pulverization is relatively thorough and the obtained powder is mostly micropolymer chain segments. Figure 2 and Figure 3 It can be seen that both the powder-containing and powder-free foams formed a complete cellular structure without powder agglomeration, which further indicates that the micropowder is evenly distributed. Figure 4 As shown in the figure, the activated rigid foam powder has hydrogen bond breakage and carbamate group decomposition in the high-intensity tensile extrusion stress field of polyurethane, and the decomposition product contains -OH structure. -1 The main reasons for the enhancement of vibration peaks are: 1. Breaking of -NH- hydrogen bond; 2. Production of -OH; 2278cm -1 The -NCO vibration peak weakened because the -NCO produced by the original main chain and mechanical chemical decomposition reacted with water to form amine groups under thermal oxygen conditions.

[0035] In addition, the polyurethane powder currently prepared by physical methods generally adopts the process of adding powder outside the third component system for foaming. The main reason is that there are process difficulties such as agglomeration and sedimentation of solid powder after mixing into the combined white material, and clogging of the equipment filter screen due to uneven mixing. The foam prepared after application also generally has the problem of performance and quality degradation.

[0036] The innovation of the above technical solution of the present invention lies in: ① Waste rigid polyurethane foam is crushed to a particle size distribution of DV (90) ≤ 150 μm (the particle size range is lower than the requirements of the prior art), the micropowder has a hydroxyl value, exists as a chain segment at the microscopic level, and the pores disappear. It replaces polyether polyol in a certain proportion and is mixed into the white material to obtain a white material composition containing micropowder; ② A specific mixing process is used to prepare a combined white material formula containing micropowder in a proportion range of 5%-30%. Among them, the third mixture can be stored under the conditions of maintaining pressure and stirring speed, and the third mixture is the mixed combined white material formula. The combined white material formula obtained under this mixing process has the characteristics of good solid-liquid dispersion uniformity and no agglomeration and sedimentation; when the white material passes through the high-pressure foaming machine or the premixing station filter, the filter screen will not be blocked, which solves a major problem in the industry.

[0037] In a preferred embodiment, the high boiling point foaming agent is a foaming agent with a boiling point greater than 5° C., and the low boiling point foaming agent is a foaming agent with a boiling point less than 0° C. Further, the high boiling point foaming agent is selected from at least one of cyclopentane, isopentane, 245FA, and LBA; and the low boiling point foaming agent is selected from at least one of R600 and R600a.

[0038] In a preferred embodiment, it also includes a foaming step, wherein the foaming material temperature of the foaming step is ≥25°C, and the gun head pressure is ≥140bar. The polyurethane foam is prepared by foaming under specific process conditions, and the specific method is as follows: the foaming material containing activated rigid foam powder is transported to a high-pressure foaming machine for material liquid circulation, preferably the low-pressure circulation pressure is ≥5bar, and the material tank stirring system is started; the foaming is carried out under the conditions of injection pressure ≥120bar, preferably ≥140bar, and material temperature ≥10°C, preferably ≥25°C, to solve the problem of mixing uniformity of high-viscosity foam materials, and foaming is carried out under high pressure and high material temperature conditions to solve the problem of mixing reaction uniformity of high-viscosity combined white materials and black materials. During the foaming process, the aforementioned combined polyether (third mixture) and organic polyisocyanate are injected into the mold cavity through the high-pressure foaming machine equipment at an overfilling rate of 1.10-1.20 to obtain polyurethane foam, improve the mixing effect, and have better foam molding quality and efficiency. With good coordination among the powder making process, the mixing process and the foaming process, the rigid polyurethane foam prepared by the present invention has excellent performance qualities such as K value, strength, defects, fluidity, demoulding efficiency, demoulding expansion rate and dimensional stability, solves the industry problem that the performance of physically recovered powders declines significantly after reuse, and has good bonding properties.

[0039] In a preferred embodiment, the polyether polyol comprises 70-100 parts, the activated rigid foam powder comprises 1-30 parts, the foaming agent comprises 1-25 parts, the water comprises 0.1-2.3 parts, the catalyst comprises 0.1-5 parts, and the surfactant comprises 0.1-2.5 parts. By controlling the amount of each raw material used in the rigid polyurethane foam, the physical property index and the appearance structure of the rigid polyurethane foam are basically the same as those of the rigid foam product without the addition of the powder.

[0040] In a preferred embodiment, the polyether polyol is prepared by reacting an initiator and an olefin oxide; the olefin oxide is selected from one or more of propylene oxide, ethylene oxide, and butylene oxide; the initiator is selected from a compound containing active hydrogen; the compound containing active hydrogen is selected from one or more of o-toluenediamine, sucrose, glycerol, vegetable oil, trimethylolpropane, pentaerythritol, sorbitol, xylitol, mannitol, methyl glucoside, ethylenediamine, and triethanolamine; the comprehensive functionality of the polyether polyol is greater than 3, and the hydroxyl value is greater than 350. Polyether polyols with high functionality and high hydroxyl value can provide sufficient crosslinking and rigidity for foams, and polyether polyols with low functionality and low hydroxyl value can provide good fluidity for foaming materials. In addition, phthalic anhydride polyester polyol can also be selected as one of the combined polyols. The above polyols can be compounded according to actual needs, and preferably the combined polyether polyol has a comprehensive functionality greater than 3 and a hydroxyl value greater than 350 to obtain better foam performance.

[0041] In a preferred embodiment, the catalyst includes a composition of a foaming catalyst, a gel catalyst and a polymerization catalyst; the foaming catalyst is selected from at least one of pentamethyldiethylenetriamine, bis-dimethylaminoethyl ether, N-methyldicyclohexylamine, and tetramethylhexanediamine; the gel catalyst is 1,2-dimethylimidazole or a mixture of 1,2-dimethylimidazole and at least one of dimethylcyclohexylamine and dimethylbenzylamine; the polymerization catalyst is selected from at least one of isooctyl ester, potassium acetate, 1,3,5-tris(dimethylaminopropyl)hexahydrotriazine, (2-hydroxypropyl), trimethylammonium formate, ethyl quaternary ammonium salt, and octyl quaternary ammonium salt; the surfactant is selected from at least one of silicone oil L6863, silicone oil L6988, L-6952, silicone oil AK8830, silicone oil B8525, silicone oil B8545, Meside's AK8812 or Meside's AK8809. The polyurethane foam prepared by adopting the above formula has the advantages of fast curing speed, low density, low thermal conductivity, good dimensional stability, fast demoulding, good environmental performance and high strength.

[0042] On the other hand, the present invention provides a polyurethane foam, which is prepared by the preparation method of the polyurethane foam described in any of the above technical solutions. The active hard foam powder used in the raw materials of the above polyurethane foam is obtained by repeated extrusion and crushing of waste hard polyurethane foam, and its particle size is evenly distributed, and the particle size distribution reaches the level of DV (90) ≤ 150 μm, and it has terminal activity, can react with polyurethane, and is mixed into the combined white material in a certain proportion under a specific mixing process, and the combined white material is transported to the high-pressure foaming machine for circulation, which solves the problems of uniformity of solid recovery powder mixed into the white material, clogging of the equipment filter and sedimentation of the powder in the industry; foaming is carried out under certain process range conditions to prepare hard polyurethane foam and refrigerators containing foam, and the foam has the advantages of low K value, low density, high strength, good demoulding and good adhesion. Under the good coordination of formula and process conditions, the industry problem of serious degradation and attenuation of foam performance and quality after solid powder recovery and application is solved, and the appearance of the refrigerator prepared by the polyurethane foam is qualified.

[0043] The present invention also provides a refrigerator, wherein the foam of the refrigerator is selected from the polyurethane foam described in the above technical solution. The refrigerator uses active hard foam powder obtained by crushing waste hard polyurethane foam to replace part of the polyether polyol, thereby realizing the recycling of waste hard polyurethane foam and ensuring the performance requirements of the polyurethane foam used for the refrigerator. The refrigerator uses a small amount of foam and has good environmental protection, and can ensure the flatness of the product after demolding in a short time. Compared with the existing box foaming composition containing recycled solid powder, the demolding time of the quick demolding foaming composition of the present invention applied to the box foaming is less than 150s, and can even reach less than 100s; the thermal conductivity at an average temperature of 10°C can be 18.5-18.9mw / mK.

[0044] In order to more clearly and in detail introduce a polyurethane foam, a preparation method thereof and a refrigerator provided by the embodiments of the present invention, they will be described below in conjunction with specific embodiments.

[0045] 1. Provide an embodiment of the mixing step

[0046] The definitions of terms involved in the mixing process are as follows

[0047] Filter retention rate: (weight of combined white material after passing through the filter - weight before passing through the filter) / weight of solid powder * 100

[0048] Viscosity deviation rate: ① Test the viscosity at the top, middle and bottom of the liquid, which are recorded as a, b and c respectively;

[0049] ② Filter the minimum viscosity value and the maximum viscosity value, (maximum-minimum) / minimum*100, and record it as the viscosity deviation rate; this parameter mainly measures the viscosity distribution at different positions.

[0050] Specific implementation cases

[0051] Example 1

[0052] Combine 90 parts of polyether polyol, 2 parts of catalyst, 2 parts of silicone oil surfactant, and 2.1 parts of water to form a first mixture;

[0053] Cyclopentane cp 14 parts LBA or 245fa 7.5 parts, the above components and the first mixture were stirred for 30 minutes to obtain a second mixture;

[0054] 10 parts of activated rigid foam powder (DV(90)=150 microns) and 1.5 parts of R600 are added. The above components and the second mixture are stirred at a temperature of 30° C. and a pressure of 4 bar for 30 minutes to obtain a third component liquid.

[0055] The third component liquid was subjected to a filter passability test (filter diameter: 80 mesh, 177 microns). After passing through 50 times, the filter retention rate was tested; and the viscosity deviation rate of the third component was tested.

[0056] Example 2

[0057] Combine 90 parts of polyether polyol, 2 parts of catalyst, 2 parts of silicone oil surfactant, and 2.1 parts of water to form a first mixture;

[0058] 14 parts of cyclopentane cp, 7.5 parts of LBA or 245fa, the above components and the first mixture were stirred for 30 minutes to obtain a second mixture;

[0059] 10 parts of activated rigid foam powder (DV(90)=150 microns) and 1.5 parts of R600 are added. The above components and the second mixture are stirred at a temperature of 30° C. and a pressure of 4 bar for 60 minutes to obtain a third component liquid.

[0060] The third component liquid was subjected to a filter passability test (filter diameter: 80 mesh, 177 microns). After passing through 50 times, the filter retention rate was tested; and the viscosity deviation rate of the third component was tested.

[0061] Example 3

[0062] Combine 80 parts of polyether polyol, 2 parts of catalyst, 2 parts of silicone oil surfactant, and 2.1 parts of water to form a first mixture;

[0063] 14 parts of cyclopentane cp, 7.5 parts of LBA or 245fa, the above components and the first mixture were stirred for 30 minutes to obtain a second mixture;

[0064] 20 parts of activated rigid foam powder (DV(90)=150 microns) and 1.5 parts of R600 are added. The above components and the second mixture are stirred at a temperature of 30° C. and a pressure of 4 bar for 30 minutes to obtain a third component liquid.

[0065] The third component liquid was subjected to a filter passability test (filter diameter: 80 mesh, 177 microns). After passing through 50 times, the filter retention rate was tested; and the viscosity deviation rate of the third component was tested.

[0066] Example 4

[0067] Combine 90 parts of polyether polyol, 2 parts of catalyst, 2 parts of silicone oil surfactant, and 2.1 parts of water to form a first mixture;

[0068] 14 parts of cyclopentane cp, 7.5 parts of LBA or 245fa, the above components and the first mixture were stirred for 30 minutes to obtain a second mixture;

[0069] 10 parts of activated rigid foam powder (DV(90)=60 microns) and 1.5 parts of R600 are added. The above components and the second mixture are stirred at a temperature of 30° C. and a pressure of 4 bar for 30 minutes to obtain a third component liquid.

[0070] The third component liquid was subjected to a filter passability test (filter diameter: 80 mesh, 177 microns). After passing through 50 times, the filter retention rate was tested; and the viscosity deviation rate of the third component was tested.

[0071] Example 5

[0072] Combine 90 parts of polyether polyol, 2 parts of catalyst, 2 parts of silicone oil surfactant, and 2.1 parts of water to form a first mixture;

[0073] 14 parts of cyclopentane cp, 7.5 parts of LBA or 245fa, the above components and the first mixture were stirred for 30 minutes to obtain a second mixture;

[0074] 10 parts of activated rigid foam powder (DV(90)=170 microns) and 1.5 parts of R600 are added. The above components and the second mixture are stirred at a temperature of 30° C. and a pressure of 4 bar for 30 minutes to obtain a third component liquid.

[0075] The third component liquid was subjected to a filter passability test (filter diameter: 80 mesh, 177 microns). After passing through 50 times, the filter retention rate was tested; and the viscosity deviation rate of the third component was tested.

[0076] Comparative Example 1

[0077] Combine 90 parts of polyether polyol, 2 parts of catalyst, 2 parts of silicone oil surfactant, and 2.1 parts of water to form a first mixture;

[0078] 10 parts of activated rigid foam powder (DV(90)=150 microns), the above components and the first mixture were stirred for 30 minutes to obtain a second mixture;

[0079] R600 1.5 parts, cyclopentane cp 14 parts, LBA or 245fa 7.5 parts, the above components and the second mixture are stirred at a temperature of 30° C. and a pressure of 4 bar for 30 minutes to obtain a third component liquid.

[0080] The third component liquid was subjected to a filter passability test (filter diameter: 80 mesh, 177 microns). After passing through 50 times, the filter retention rate was tested; and the viscosity deviation rate of the third component was tested.

[0081] Comparative Example 2

[0082] Combine 90 parts of polyether polyol, 2 parts of catalyst, 2 parts of silicone oil surfactant, and 2.1 parts of water to form a first mixture;

[0083] 10 parts of activated rigid foam powder (DV(90)=150 microns), the above components and the first mixture were stirred for 90 minutes to obtain a second mixture;

[0084] R600 1.5 parts, cyclopentane cp 14 parts, LBA or 245fa 7.5 parts, the above components and the second mixture are stirred at a temperature of 30° C. and a pressure of 4 bar for 30 minutes to obtain a third component liquid.

[0085] The third component liquid was subjected to a filter passability test (filter diameter: 80 mesh, 177 microns). After passing through 50 times, the filter retention rate was tested; and the viscosity deviation rate of the third component was tested.

[0086] Comparative Example 3

[0087] Combine 90 parts of polyether polyol, 2 parts of catalyst, 2 parts of silicone oil surfactant, and 2.1 parts of water to form a first mixture;

[0088] 14 parts of cyclopentane cp, 7.5 parts of LBA or 245fa, the above components and the first mixture were stirred for 30 minutes to obtain a second mixture;

[0089] 10 parts of activated rigid foam powder (DV(90)=150 microns) and 1.5 parts of R600 are added. The above components and the second mixture are stirred at a temperature of 10° C. and a pressure of 1 bar for 30 minutes to obtain a third component liquid.

[0090] The third component liquid was subjected to a filter passability test (filter diameter: 80 mesh, 177 microns). After passing through 50 times, the filter retention rate was tested; and the viscosity deviation rate of the third component was tested.

[0091] Comparative Example 4

[0092] Combine 90 parts of polyether polyol, 2 parts of catalyst, 2 parts of silicone oil surfactant, and 2.1 parts of water to form a first mixture;

[0093] 14 parts of cyclopentane cp, 7.5 parts of LBA or 245fa, the above components and the first mixture were stirred for 30 minutes to obtain a second mixture;

[0094] 10 parts of activated rigid foam powder (DV(90)=150 microns) and 1.5 parts of R600 are added. The above components and the second mixture are stirred at a temperature of 10° C. and a pressure of 1 bar for 90 minutes to obtain a third component liquid.

[0095] The third component liquid was subjected to a filter passability test (filter diameter: 80 mesh, 177 microns). After passing through 50 times, the filter retention rate was tested; and the viscosity deviation rate of the third component was tested.

[0096] Comparative Example 5

[0097] Combine 100 parts of polyether polyol, 2 parts of catalyst, 2 parts of silicone oil surfactant, and 2.1 parts of water to form a first mixture;

[0098] 14 parts of cyclopentane cp, 7.5 parts of LBA or 245fa, the above components and the first mixture were stirred for 30 minutes to obtain a second mixture;

[0099] R600 1.5 parts, the above components and the second mixture were stirred at a temperature of 30°C and a pressure of 4 bar for 30 minutes to obtain a third component liquid.

[0100] The third component liquid was subjected to a filter passability test (filter diameter: 80 mesh, 177 microns). After passing through 50 times, the filter retention rate was tested; and the viscosity deviation rate of the third component was tested.

[0101] Performance Testing

[0102] The performance test results of the above embodiments 1-5 and comparative examples 1-5 are shown in Table 1.

[0103] Table 1 Mixing conditions of embodiments and comparative examples

[0104]

[0105] It can be seen from the above table Examples 1-2 that when the mixing time is ≥30 min, the filter retention rate is low, the filter is almost not blocked, and the viscosity deviation rate is low, indicating that the powder is evenly distributed at various positions; properly increasing the mixing time can obtain a better mixing effect.

[0106] It can be seen from Example 3 in the above table that when the proportion of activated micropowder increases, the filter retention rate and the viscosity deviation rate increase slightly, but the overall values ​​are low, indicating that the powder is distributed more evenly at various positions; the probability of clogging the filter is also small; it mainly affects the overall viscosity of the foam material and has a greater impact on the mixing of the gun head of the foaming equipment.

[0107] It can be seen from Examples 1, 4 and 5 in the above table that the smaller the particle size, the lower the filter retention rate, the lower the probability of filter clogging, and the lower the viscosity deviation rate, indicating that the powder is more evenly distributed at various positions.

[0108] It can be seen from the comparative examples 1-2 in the above table that after changing the mixing steps, the filter retention rate and the viscosity deviation rate both increased, increasing the probability of filter blockage and worsening the mixing uniformity; the mixing time needs to be increased to improve the mixing uniformity, which seriously reduces the mixing efficiency.

[0109] It can be seen from the comparative examples 3-4 in the above table that after reducing the mixing temperature and pressure, the filter retention rate and viscosity deviation rate both increase, increasing the probability of filter blockage and worsening the mixing uniformity; the mixing time needs to be increased to improve the mixing uniformity, which seriously reduces the mixing efficiency; in addition, the viscosity value increases significantly, mainly due to the volatilization of the foaming agent after the pressure is reduced.

[0110] It can be seen from the comparative examples 1, 2, 4 and 5 in the above table that, under the premise of controlling the mixing steps and process parameters recommended by the present invention, the uniformity of the combined white material and the filter combination rate obtained by mixing the powder-containing foam material are slightly increased compared with those without activated micropowder, but are generally at a good level. When used in the refrigerator field, it has little impact on the equipment in actual production, and can achieve good matching with the equipment.

[0111] Description of foaming process parameters: material temperature>15°C, preferably>25°C, reduce the viscosity at the mixing gun tip, gun tip pressure>100bar, preferably>140bar, improve the mixing effect of the high viscosity foaming system gun tip, no special requirements for other foaming parameters, just meet the general process parameter requirements of rigid foaming.

[0112] 2. Provide an embodiment of refrigerator foam

[0113] The beneficial effects of the polyurethane foam of the present invention are as follows:

[0114] 1. Add recycled waste rigid polyurethane foam activated micro powder into the combined white material. The powder has good mixing uniformity, does not agglomerate and settle, and can pass through the high-pressure foaming machine filter (≥200 micron filter diameter) without clogging, and has good equipment matching.

[0115] 2. After adding activated micropowder in the present invention, the foam performance does not decrease but increases, and the prepared polyurethane foam has low density, good thermal insulation performance, high demoulding efficiency, and small demoulding deformation rate.

[0116] 3. The polyurethane foam prepared by the present invention has good mechanical properties, small expansion rate, rapid demoulding (the demoulding time can be less than 150s), high production efficiency, and strong economic applicability.

[0117] The above polyurethane foam refrigerator industry has great economic benefits. In the present invention, unless otherwise specified, the various terms in the present invention are defined as follows:

[0118] Just Fill Weight (MFW): The minimum weight required to completely fill the mold, in grams;

[0119] Molded core density: the effective density of the foam, i.e. the core density of the foam without the crust;

[0120] Filling rate: injection weight*100 / MFW, unit: %;

[0121] Fiber time: the time from the start of mixing until the rod placed in the foam stretches out the fibers when removed;

[0122] Free foam density: the density of foam prepared by foaming in a free state (without a mold);

[0123] Demoulding time: the time from foam injection to mould opening;

[0124] Thermal conductivity λ: measured according to ISO 12939-01 / DIN 52612 using a TA FOX-200 thermal conductivity meter at an average temperature of 10°C (upper plate 2°C, lower plate 18°C). 24 hours after foam preparation, foam samples were cut from the center of the molded part and measured immediately after cutting, unit: mW / m·K;

[0125] Foam compression strength: measured according to DIN 53421-06-84, unit KPa;

[0126] Dimensional stability: The dimensional change of the foam after being measured at a low temperature of -30°C for 24 hours, in %;

[0127] Expansion rate: Foam expansion rate is a way to detect the level of foam curing. The expansion rate is calculated as follows, in %. In the present invention, the expansion rate of the foam material made by the H-Mould mold is measured.

[0128] Expansion rate = (maximum foam thickness after demoulding - mold thickness) / mold thickness × 100%;

[0129] Degree of stickiness: represents the level of foam maturation within a certain demoulding time, and is divided into three levels: A, B, and C. A means that the mold is completely non-sticky and the maturation is good; B means slight stickiness and general maturation; C means severe stickiness and poor maturation.

[0130] Specific implementation cases

[0131] Example 1

[0132] Combine polyether polyol 90 parts, activated rigid foam powder 10 parts (DV (90) = 150 microns), cyclopentane CP 14 parts, LBA or 245FA 7.5 parts, low boiling point foaming agent R600 1.6 parts, catalyst 2 parts, silicone oil surfactant 2 parts, water 2.1 parts, polymerized MDI 156 parts;

[0133] The mixing was carried out according to the mixing steps of the above mixing embodiment, wherein the mixing temperature was 30° C., the mixing pressure was 4 bar, and the mixing time was 60 min; the foaming material temperature was 25° C., and the gun tip pressure was 140 bar.

[0134] Example 2

[0135] The composition includes 90 parts of polyether polyol, 10 parts of activated rigid foam powder (DV(90)=170 microns), 14 parts of cyclopentane CP, 7.5 parts of LBA or 245FA, 1.6 parts of low boiling point blowing agent R600, 2 parts of catalyst, 2 parts of silicone oil surfactant, 2.1 parts of water, and 156 parts of polymerized MDI.

[0136] The mixing was carried out according to the mixing steps of the above mixing embodiment, wherein the mixing temperature was 30° C., the mixing pressure was 4 bar, and the mixing time was 60 min; the foaming material temperature was 25° C., and the gun tip pressure was 140 bar.

[0137] Example 3

[0138] The composition includes 80 parts of polyether polyol, 20 parts of activated rigid foam powder (DV(90)=150 microns), 14 parts of cyclopentane CP, 7.5 parts of LBA or 245FA, 1.6 parts of low boiling point blowing agent R600, 2 parts of catalyst, 2 parts of silicone oil surfactant, 2.1 parts of water, and 156 parts of polymerized MDI.

[0139] The mixing was carried out according to the mixing steps of the above mixing embodiment, wherein the mixing temperature was 30° C., the mixing pressure was 4 bar, and the mixing time was 60 min; the foaming material temperature was 25° C., and the gun tip pressure was 140 bar.

[0140] Example 4

[0141] The composition includes 90 parts of polyether polyol, 10 parts of activated rigid foam powder (DV(90)=60 microns), 14 parts of cyclopentane CP, 7.5 parts of LBA or 245FA, 1.6 parts of low boiling point blowing agent R600, 2 parts of catalyst, 2 parts of silicone oil surfactant, 2.1 parts of water, and 156 parts of polymerized MDI.

[0142] The mixing was carried out according to the mixing steps of the above mixing embodiment, wherein the mixing temperature was 30° C., the mixing pressure was 4 bar, and the mixing time was 60 min; the foaming material temperature was 25° C., and the gun tip pressure was 140 bar.

[0143] Example 5

[0144] The composition includes 90 parts of polyether polyol, 10 parts of activated rigid foam powder (DV(90)=150 microns), 14 parts of cyclopentane CP, 7.5 parts of LBA or 245FA, 1.6 parts of low boiling point blowing agent R600, 2 parts of catalyst, 2 parts of silicone oil surfactant, 2.1 parts of water, and 156 parts of polymerized MDI.

[0145] The mixing was carried out according to the mixing steps of the above mixing embodiment, wherein the mixing material temperature was 15° C., the mixing pressure was 1 bar, and the mixing time was 20 min; the foaming material temperature was 25° C., and the gun head pressure was 140 bar.

[0146] Example 6

[0147] The composition includes 90 parts of polyether polyol, 10 parts of activated rigid foam powder (DV(90)=150 microns), 14 parts of cyclopentane CP, 7.5 parts of LBA or 245FA, 1.6 parts of low boiling point blowing agent R600, 2 parts of catalyst, 2 parts of silicone oil surfactant, 2.1 parts of water, and 156 parts of polymerized MDI.

[0148] The mixing was carried out according to the mixing steps of the above mixing embodiment, wherein the mixing temperature was 30° C., the mixing pressure was 4 bar, and the mixing time was 60 min; the foaming material temperature was 15° C., and the gun tip pressure was 100 bar.

[0149] Example 7

[0150] Combine 90 parts of polyether polyol, 10 parts of activated rigid foam powder (DV (90) = 150 microns), 15 parts of cyclopentane cp, 2 parts of catalyst, 2 parts of silicone oil surfactant, 2.1 parts of water, and 156 parts of polymerized MDI.

[0151] The mixing was carried out according to the mixing steps of the above mixing embodiment, wherein the mixing temperature was 30° C., the mixing pressure was 4 bar, the mixing time was 60 min, the foaming material temperature was 25° C., and the gun head pressure was 140 bar.

[0152] Comparative Example 1

[0153] The composite polyether polyol is 100 parts, cyclopentane CP is 14 parts, LBA or 245FA is 7.5 parts, low boiling point foaming agent R600 is 0 parts, low boiling point foaming agent R600 A is 0 parts, DMI is 0 parts, K15 is 0 parts, other catalysts are 3.5 parts, silicone oil surfactant is 2 parts, water is 2.1 parts, and polymerized MDI is 155 parts.

[0154] The mixing was carried out according to the mixing steps of the above mixing embodiment, wherein the foaming material temperature was 25° C. and the gun tip pressure was 140 bar.

[0155] Comparative Example 2

[0156] 80 parts of combined polyether polyol, 10 parts of activated rigid foam powder (DV (90) = 150 microns) (not mixed into the combined white material, poured into the mold in advance, and used for foaming outside the system), 14 parts of cyclopentane CP, 7.5 parts of LBA or 245FA, 0 parts of low boiling point foaming agent R600, 0 parts of low boiling point foaming agent R600 A, 2.5 parts of catalyst, 2 parts of silicone oil surfactant, 2.1 parts of water, and 155 parts of polymerized MDI.

[0157] The foaming material temperature is 25°C and the gun tip pressure is 140 bar.

[0158] Performance Testing

[0159] The combined polyether prepared in Examples 1-8 and Comparative Examples 1-2 was respectively mixed with organic polyisocyanate (PM-200) in a weight ratio of 1:1.20, and injected into a cavity mold (the mold had a size of 2000×400×50mm (length×width×height), and had a vent hole on the top to discharge the gas generated in the mold in time during the foaming process). After aging for 300s, the mold was opened to obtain polyurethane foam.

[0160] (I) The foam produced in the Langzhi mold can be used to measure thermal conductivity, compressive strength, and molded core density;

[0161] (II) Injecting the combined polyether and organic polyisocyanate into an H-Mould mold with a size of 700×500×100 mm using the same method, the obtained foam is used to test the demoulding property and expansion rate of the foam, and the mold temperature is about 45°C;

[0162] The test results are shown in Table 2 below.

[0163] Table 2 Foam performance test results

[0164]

[0165]

[0166] It can be seen from Examples 1-7 in Table 2 above that the foams prepared by adding the rigid foam activation powder to the high viscosity, high hydroxyl value polyether polyol and multi-component foaming agent system have a relatively low core density. When mixed with a low boiling point foaming agent, the density can be lower than 29.5 kg / m 3 ; Without low boiling point conditions, the density is also lower than 35kg / m 3 , and has good economic value as a whole.

[0167] It can be seen from Example 1 and Example 4 in Table 2 above that when the activated micropowder particle size distribution DV (90) ≤ 150 microns, the rigid polyurethane foam prepared under the optimal mixing process and foaming process parameter control conditions has better thermal insulation performance, strength performance, and demolding performance, which are basically at the same level as the comparative example 1 without micropowder foam.

[0168] It can be seen from Example 2 in Table 2 above that when the particle size distribution DV(90) is greater than 150 μm, the overall performance of the foam decreases significantly, especially the K value deteriorates significantly, indicating that a smaller and more uniform particle size distribution has a greater impact on the K value.

[0169] It can be seen from Example 5 in Table 2 above that the control of mixing process parameters has a great influence on the quality of foam molding. The increase in free bubble density is due to insufficient pressure holding and volatilization of high-boiling point foaming agent. The decrease in foam performance is mainly related to mixing temperature and mixing time. Uneven mixing of material and liquid leads to uneven viscosity distribution, which affects foam material mixing.

[0170] It can be seen from Example 6 in Table 2 above that the control of foaming process parameters has a great influence on the quality of foam molding. The main reason is that low material temperature and low foaming pressure are not conducive to the mixing of high viscosity foam material systems.

[0171] It can be seen from Comparative Example 2 in Table 2 above that the effect of adding activated micropowder outside the system is not as good as that of mixing it into the prepared white material through the mixing process.

[0172] The polyurethane foams prepared in the following Examples 1-3 and Comparative Example 1 were used as thermal insulation materials in refrigerators, and the performance of the refrigerators was tested. Specifically, two refrigerators of the same model were prepared in Examples 1-3 and Comparative Example 1, and the demoulding time was 150 seconds.

[0173] The properties of the prepared foam are shown in Table 3. After the refrigerator is demoulded, the difference between the thickness of the left and right sides of the box at the top, middle and bottom and the thickness of the corresponding position of the foamed box is measured, that is, the deformation of the box before and after the refrigerator is demoulded (in mm), and the average value is taken at each location. The maximum and minimum difference at each location should be less than 2 mm.

[0174] High and low temperature test of the cabinet: -30℃24h, 50℃24h alternating ambient temperature changes once for one cycle, a total of 4 cycles. Mainly test whether the polyurethane foam and the refrigerator liner and shell are debonded under the impact of high and low temperature extreme environments, and judge the degree of foam maturation and adhesion.

[0175] Table 3 Comparison of refrigerator foam performance between Examples 1-3 and Comparative Example 1

[0176] project unit Example 1 Example 2 Comparative Example 1 Thermal conductivity mw / mk 18.80 18.60 18.50 Left side-top mm 1.88 1.65 1.57 Left side-middle mm 1.95 1.78 1.83 Left side-bottom mm 1.93 1.59 1.56 Right side-top mm 1.95 1.80 1.76 Right side - middle mm 1.89 1.86 1.78 Right side-bottom mm 1.74 1.56 1.74 High and low temperature test of the box Eligibility qualified qualified qualified

[0177] As shown in Table 3, the refrigerator boxes produced by Examples 1-2 using the activated micropowder polyol composition as the insulation material can meet the product performance requirements. The appearance deformation of the box is basically at the same level as that of Comparative Example 1. No debonding phenomenon occurs in the high and low temperature impact test, indicating that the foam has good adhesion.

Claims

1. A method for preparing polyurethane foam, for preparing polyurethane foam used as refrigerator foam, characterized in that: The method comprises a mixing step, wherein the mixing step further comprises: The first mixture preparation step comprises mixing polyether polyol, water, a catalyst and a foaming aid to obtain a first mixture; A second mixture preparation step, comprising mixing a high boiling point blowing agent into the first mixture to obtain a second mixture; The third mixture preparation step comprises adding the activated rigid foam powder to the second mixture, and adding a low-boiling point foaming agent after mixing under pressure in a mixing device, and continuing to mix under pressure to obtain a third mixture; during the preparation of the third mixture, the mixing device provides multi-directional shear force to the mixture and maintains a stirring state, the stirring speed is greater than 1000 rpm, the mixing temperature is greater than 10°C, and the pressure of the pressure-maintaining mixing is greater than 2 bar; The viscosity of the polyether polyol is greater than 1000 mPa.s; the activated rigid foam micropowder is obtained by crushing rigid polyurethane foam waste and has terminal active hydroxyl groups, and the particle size distribution DV(90) of the activated rigid foam micropowder is ≤150 μm.

2. The method for preparing polyurethane foam according to claim 1, characterized in that: The high boiling point foaming agent is a foaming agent with a boiling point greater than 5°C, and the low boiling point foaming agent is a foaming agent with a boiling point less than 0°C.

3. The method for preparing polyurethane foam according to claim 2, characterized in that: The high boiling point foaming agent is selected from at least one of cyclopentane, isopentane, 245FA, and LBA; the low boiling point foaming agent is selected from at least one of R600 and R600a.

4. The method for preparing polyurethane foam according to claim 1, characterized in that: During the preparation of the third mixture, the mixing temperature is ≥30° C., the pressure of the pressure-maintaining mixing is >4 bar, and the mixing time is ≥30 minutes.

5. The method for preparing polyurethane foam according to claim 1, characterized in that: The method further comprises a foaming step, wherein the foaming material temperature in the foaming step is ≥25°C and the gun head pressure is ≥140 bar.

6. The method for preparing polyurethane foam according to claim 1, characterized in that: Calculated by weight, it includes 70-100 parts of polyether polyol, 1-30 parts of activated rigid foam powder, 1-25 parts of foaming agent, 0.1-2.3 parts of water, 0.1-5 parts of catalyst and 0.1-2.5 parts of surfactant.

7. The method for preparing polyurethane foam according to claim 1, characterized in that: The polyether polyol is prepared by reacting an initiator and an olefin oxide; the olefin oxide is selected from one or more of propylene oxide, ethylene oxide, and butylene oxide; the initiator is selected from a compound containing active hydrogen; the compound containing active hydrogen is selected from one or more of o-toluenediamine, sucrose, glycerol, vegetable oil, trimethylolpropane, pentaerythritol, sorbitol, xylitol, mannitol, methyl glucoside, ethylenediamine, and triethanolamine; the comprehensive functionality of the polyether polyol is greater than 3, and the hydroxyl value is greater than 350.

8. The method for preparing polyurethane foam according to claim 6, characterized in that: The catalyst includes a composition of a foaming catalyst, a gel catalyst and a polymerization catalyst; the foaming catalyst is selected from at least one of pentamethyldiethylenetriamine, bis-dimethylaminoethyl ether, N-methyldicyclohexylamine, and tetramethylhexanediamine; the gel catalyst is 1,2-dimethylimidazole or a mixture of 1,2-dimethylimidazole and at least one of dimethylcyclohexylamine and dimethylbenzylamine; the polymerization catalyst is selected from at least one of isooctyl ester, potassium acetate, 1,3,5-tris(dimethylaminopropyl)hexahydrotriazine, (2-hydroxypropyl), trimethylammonium formate, ethyl quaternary ammonium salt, and octyl quaternary ammonium salt; the surfactant is selected from at least one of silicone oil L6863, silicone oil L6988, L-6952, silicone oil AK8830, silicone oil B8525, silicone oil B8545, Meside's AK8812, or Meside's AK8809.

9. A polyurethane foam, characterized in that: The polyurethane foam is prepared by the method for preparing the polyurethane foam according to any one of claims 1 to 8.

10. A refrigerator, characterized in that: The foam of the refrigerator is selected from the polyurethane foam described in claim 9.

Citation Information

Patent Citations

  • Rigid polyurethane foam plastic as well as preparation method and application thereof

    CN113817128A